THE EFFECT OF DISTRIBUTION OF UMKM FINANCING BY BPRS RAHMA HIJRAH AGUNG ON THE GROWTH OF THE UMKM INDUSTRY AND EMPLOYMENT IN LHOKSEUMAWE CITY - Aulannisa Syuda; Teuku Zulkarnain; Ahmad Fauzan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Small Micro and Medium Enterprises (UMKM) have a role as one of the tools for community empowerment to optimize agricultural products, especially small or rural communities. Processing carried out by UMKM is able to add economic value and benefits to the community and its region. The purpose of the study is to determine the effect of the distribution of BPRS Rahma Hijrah Agung funds on the growth of UMKM and labor absorption in the city of Lhokseumawe. The method used in this study is a quantitative method. The source of data collection uses publication data from the Central Statistics Agency and data on the distribution of UMKM funds sourced from BPRS Rahma Hijrah Agung. The variables in the scope of this study use time series data, consisting of independent and dependent variables. The focus of the research observation is on data on fund distribution (X) as well as UMKM growth (Y1) and labor absorption (Y2). The data analysis technique uses simple linear regression analysis, previously a classical assumption test was carried out. The results of the t-test show that the distribution of UMKM funds at BPRS Rahma Hijrah Agung has a direct and significant effect on the growth of UMKM and the absorption of labor in Lhokseumawe City.